Admiral Ushakov Marine State University - V. V. Butenko (Известия высших учебных заведений России: Радиоэлектроника)
An algorithm for search boundaries of iris it as a point of interest in the tracking direction of view in video stream. It is the first of a planned series of publications that illustrate creation of control system using available view video equipment.